Population Aging and its Macroeconomic Implications : A Framework for Analysis - Faruqee, Hamid (IMF Working Papers; Working Paper ;, 2002)
This paper develops a model to examine the macroeconomic implications of population aging. Using a general equilibrium framework, the analysis examines the various channels through which changes in demographics affect the economy. Age-earnings profiles are taken to summarize differences in effective labor supply across age groups and to help determine changes in consumption and saving behavior that occur over an agent's lifetime. Aggregating these supply- and demand-side effects, the implications of aging on economic activity and fiscal policy are then examined.